SISTEM CERDAS PENGURAS AIR AKUARIUM SECARA OTOMATIS BERBASIS INTERNET oF THINGS (IoT) MENGGUNAKAN ALGORITMA C4.5 pada PLATFORM BLYNK - Nurhakim, Muhamad Wilvan; Wijaya, Anderias Eko; Hermawan, Rian (STMIK Subang, 2024)
In general, fishkeeping has been a widely cherished activity among communities since ancient times, owing to its ease of maintenance and care, which encourages many individuals to engage in it. However, due to busy schedules or unforeseen circumstances, checking the water conditions in aquariums often poses a challenge. Therefore, there is a need for a tool capable of automatically controlling and draining aquarium water based on IoT technology using the C4.5 algorithm on the Blynk platform. This system can drain water if the aquarium water becomes cloudy, raise the temperature if it drops below optimal levels, and limit water filling. The ESP8266 and ESP32-S modules are utilized to receive, process, and transmit data to the aquarium owner via Wi-Fi. Relays serve as electrical power distributors for supporting components such as water pumps, water heaters, and solenoid valves. Testing results indicate that the water condition control component effectively operates in line with the system's functions and objectives. The existence of this tool can assist fishkeepers in maintaining real-time aquarium water quality, detecting water pollution, and monitoring the health of fish within the aquarium.